Efficacy and safety of oral sodium bicarbonate in kidney-transplant recipients and non-transplant patients with chronic kidney disease: a systematic review and meta-analysis - Wu, Yun; Wang, Ying; Huang, Weijun; Guo, Xi; Hou, Baoluo; Tang, Jingyi; Wu, Yuqi; Zheng, Huijuan; Pan, Yanling; Liu, Wei Jing (Frontiers in Pharmacology, 2024)
We investigated the efficacy and safety of oral sodium bicarbonate in kidneytransplant recipients and non-transplant patients with chronic kidney disease (CKD), which are currently unclear.Methods: PubMed, Cochrane Library, Embase, and Web of Science were searched for randomized controlled trials investigating the efficacy and safety of sodium bicarbonate versus placebo or standard treatment in kidney-transplant and non-transplant patients with CKD.Results: Sixteen studies of kidney-transplant recipients (two studies, 280 patients) and non-transplant patients with CKD (14 studies, 1380 patients) were included. With non-transplant patients, sodium bicarbonate slowed kidney-function declines (standardized mean difference [SMD]: 0.49, 95% confidence interval [CI]: 0.14-0.85, P = 0.006) within ≥ 12 months (SMD: 0.75 [95% CI: 0.12-1.38], P = 0.02), baseline-serum bicarbonate < 22 mmol/L (SMD: 0.41 [95% CI: 0.19-0.64], P = 0.0004) and increased serum-bicarbonate levels (mean difference [MD]: 2.35 [95% CI: 1.40-3.30], P < 0.00001). In kidney-transplant recipients, sodium bicarbonate did not preserve graft function (SMD: -0.07 [95% CI: -0.30-0.16], P = 0.56) but increased blood pH levels (MD: 0.02 [95% CI: 0.00-0.04], P = 0.02). No significant adverse events occurred in the kidney-transplant or non-transplant patients (risk ratio [RR]: 0.89, [95% CI: 0.47-1.67], P = 0.72; and RR 1.30 [95% CI: 0.84-2.00], P = 0.24, respectively). However, oral sodium bicarbonate correlated with increased diastolic pressure and worsened hypertension and edema (MD: 2.21 [95% CI: 0.67-3.75], P = 0.005; RR: 1.44 [95% CI:1.11-1.88], P = 0.007; and RR: 1.28 [95% CI: 1.00-1.63], P = 0.05, respectively).Discussion: Oral sodium bicarbonate may slow kidney-function decline in non-transplant patients with CKD taking sodium bicarbonate supplementation for ≥12 months or a baseline serum bicarbonate level of <22 mmol/L, without preserving graft function in kidney-transplant recipients.Sodium bicarbonate may increase diastolic pressure, and elevate a higher incidence of worsening hypertension and edema.